THE ROLE OF INTELLECTUAL PROPERTY IN THE DEVELOPMENT OF INNOVATIONS IN REGENERATIVE MEDICINE. - Issa Akanji ADEDOKUN; Temidayo Peter AKEREDOLU; Olowo-Niyi ADEBOLA (ABUAD Law Journal, 2024)
Regenerative medicine marks a paradigm shift in healthcare, transitioning from symptom-based treatment to leveraging the body’s inherent healing mechanisms. It represents a convergence of nature and science, fostering innovative solutions for preserving life. Intellectual Property (IP) safeguards the expression of innovation and creativity across various domains, encompassing regenerative medicine. However, questions arise regarding its ability to meet patentability criteria and the ethical implications of granting exclusive ownership (Intellectual Property) to life-saving techniques, potentially hindering adequate Intellectual Property protection. Using the doctrinal research method, this article explores the breadth of regenerative medicine and the applicability of Intellectual Property protection to cutting-edge medical interventions, including regenerative medicine, aiming to strike a balance between comprehensive protection, commercialization, and public access. The paper draws valuable lessons from best practices and jurisdictions such as the United States of America and South Africa to promote innovation and foster access to regenerative medicine in Nigeria. It finds that one of the foremost challenges of the protection of regenerative medicine by Intellectual Property is the ethical concerns regarding the use of human cells, tissues and embryonic stem cells. It also notes some weaknesses in Nigeria’s current regulatory framework and calls for stronger enforcement of ethical standards. It recommends among others the need for more awareness in the area where intellectual property and regenerative medicine connect. The work equally advocates for the need to update the Patent and Designs Act (PDA) of 1970 to allow for the registration of cutting-edge technologies including regenerative medicine.